Doing our work better, together: a relationship-based approach to defining the quality improvement agenda in trauma care. Issue 1 (10th February 2020) - Purdy, Eve Isabelle; McLean, Darren; Alexander, Charlotte; Scott, Matthew; Donohue, Andrew; Campbell, Don; Wullschleger, Martin; Berkowitz, Gary; Winearls, James; Henry, Doug; Brazil, Victoria
Abstract : Background: Trauma care represents a complex patient journey, requiring multidisciplinary coordinated care. Team members are human, and as such, how they feel about their colleagues and their work affects performance. The challenge for health service leaders is enabling culture that supports high levels of collaboration, co-operation and coordination across diverse groups. We aimed to define and improve relational aspects of trauma care at Gold Coast University Hospital. Methods: We conducted a mixed-methods collaborative ethnography using the relational coordination survey—an established tool to analyse the relational dimensions of multidisciplinary teamwork—participant observation, interviews and narrative surveys. Findings were presented to clinicians in working groups for further interpretation and to facilitate co-creation of targeted interventions designed to improve team relationships and performance. Findings: We engaged a complex multidisciplinary network of ~500 care providers dispersed across seven core interdependent clinical disciplines. Initial findings highlighted the importance of relationships in trauma care and opportunities to improve. Narrative survey and ethnographic findings further highlighted the centrality of a translational simulation programme in contributing positively to team culture and relational ties. A range of 16 interventions—focusing on structural, process and relational dimensions—were co-created with participants and are now being implemented and evaluated by various trauma care providers. Conclusions: Through engagement of clinicians spanning organisational boundaries, relational aspects of care can be measured and directly targeted in a collaborative quality improvement process. We encourage healthcare leaders to consider relationship-based quality improvement strategies, including translational simulation and relational coordination processes, in their efforts to improve care for patients with complex, interdependent journeys.